Komunikasi Dakwah dan Pembentukan Identitas Islam dalam Komunitas Masyarakat Baduy di Kampung Mualaf Ciboleger - Fauzi, Ghaly Ihsan (Prodi KPI FDPM IPMAFA Bekerjasama dengan Mafa Press IPMAFA Pati, 2024)
The Baduy people, an ethnic minority living in the Banten region, Indonesia, were known for maintaining traditional values ​​and living a simple life. Even though they were relatively isolated from the outside world, the Baduy people cannot be separated from the influence of Islam which has become an inseparable part of their lives. The aim of this research was to analyze the role of da'wah in the formation of Islamic identity in the Baduy community who converted to Islam in Ciboleger Village. This research used ethnographic methods to observe social interactions, religious rituals and communication methods in this community. The research results showed that da'wah communication plays an important role in the process of conversion and internalization of Islamic values, as well as the formation of a new religious identity among the Bedouin community. Da'wah was carried out through individual and community approaches that emphasize religious teachings and respect for local traditions. The Islamic identity created reflects a combination of Islamic teachings and local culture, thus creating a dynamic and unique identity among the transformed Baduy community. This study contributed to understanding the process of da'wah and the formation of religious identity in the context of indigenous communities in Indonesia.